You can't live without them - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
Learn how to grow onions, garlic and leeks By P B Ngeze, Acacia Stantex Publishers - CTA Friends of the Book Foundation, 2001. 27 pp. ISBN 9966 917 20 9 CTA number 1006. 5 credit points